2014
DOI: 10.1088/0957-0233/25/5/055901
|View full text |Cite
|
Sign up to set email alerts
|

An instrument for the high temperature measurement of the Seebeck coefficient and electrical resistivity

Abstract: A system for the simultaneous measurement of thermoelectric power and resistivity of one and/or two samples over a temperature range of 300–1000 K in a vacuum chamber is designed and implemented. A sample probe is developed to provide its easy mounting and usage. In addition, two samples can be measured at the same time. Measurement accuracy has been enhanced by beadless thermocouples and micro-heaters that are specifically designed in order to minimize the ‘cold-finger effect’ and to eliminate some possible s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 35 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…In this study, non-destructive simultaneous measurements of the Seebeck coefficient and electrical resistivity of the samples were performed using a system that was developed in our laboratory for samples of different sizes in a temperature range of 300-1000 K in a vacuum chamber [50]. Using this device, we overcame possible sources of design and measurement errors such as the cold-finger effect, thermal-emf, and lead resistance [51,52].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, non-destructive simultaneous measurements of the Seebeck coefficient and electrical resistivity of the samples were performed using a system that was developed in our laboratory for samples of different sizes in a temperature range of 300-1000 K in a vacuum chamber [50]. Using this device, we overcame possible sources of design and measurement errors such as the cold-finger effect, thermal-emf, and lead resistance [51,52].…”
Section: Methodsmentioning
confidence: 99%
“…For these calculations, the measured temperature-dependent Seebeck coefficient of a platinum wire (S Pt ranging from −5.1 to −17.3 µV/K) was used as a reference from the literature [26]. The intrinsic Seebeck coefficients of silicide–oxide composites (S composite ) were calculated using the equation below:S composite//Pt = S composite −S Pt …”
Section: Resultsmentioning
confidence: 99%
“…( a ) Thermoelectric voltage and ( b ) effective Seebeck coefficients (S) measured for the [90–10] MoSi 2 -Al 2 O 3 //Pt, WSi 2 -Al 2 O 3 //Pt, TaSi 2 -Al 2 O 3 //Pt, and ZrSi 2 -Al 2 O 3 //Pt thermocouples as a function of temperature difference; and ( c ) calculated intrinsic Seebeck coefficients of the composites as a function of temperature difference (S Pt is also presented as a reference [26]).…”
Section: Figurementioning
confidence: 99%
“…Several recent reports [19,22] on the fabrication of set up to measure the S for both bulk and thin film samples relies on complex sample holder design to reduce the uncertainties in the data. Iwanaga et al [19] reported a set up which can measure the Seebeck coefficient upto 1000 K but the main complexity lies in the designing of the sample holder and placing the probes in it through drilling.…”
Section: Introductionmentioning
confidence: 99%
“…Paul [20] reported a set up for both Seebeck coefficient and electrical resistivity measurement but both the set-up are applicable till 600 K. Budngam et al [21] reported a set-up for measuring very low Seebeck co-efficient for metals for a wide range of temperature (85-1200 K). Gunes et al [22] reported a set up that also features complicated sample probe design with custom made temperature and voltage probes.…”
Section: Introductionmentioning
confidence: 99%